2020
DOI: 10.1111/bcp.14344
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of therapeutic drug monitoring of rilpivirine and its relationship with virologic response and resistance in a cohort of naive and pretreated HIV‐infected patients

Abstract: The purpose of this study was to assess the antiviral activity of the rilpivirine/emtricitabine/tenofovir disoproxil fumarate combination and to describe the pharmacokinetics of rilpivirine and its association with resistance in clinical routine. Methods: A retrospective multicentre cohort study was performed in both naive and pretreated HIV patients receiving the once-daily rilpivirine/emtricitabine/tenofovir disoproxil fumarate regimen. Immuno-virologic and resistance data, and rilpivirine plasma trough conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…These steady‐state values (C0 at all timepoints and C0avg) were above the pharmacologically active concentrations 11–13 (DTG PA‐IC90 = 0.064 μg mL −1 as well as the clinical target C0 of 0.3 μg mL −1 ; RPV PA‐IC90 = 12 ng mL −1 ) at all timepoints in both the overall population and the NNRTI subset (Figure 2). RPV C0 and Cavg were also at or above 70 ng mL −1 (the lowest C0 value of 68.91 ng mL −1 occurred at week 4 in the early‐switch group of the NNRTI subset), which was recently proposed by others as the clinical target from an observational cohort of treatment‐naive and treatment‐experienced people with HIV‐1 14 . The categorical analysis exploring the effect of age (≥50 and <50 years) on PK did not reveal any clinically meaningful differences in the DTG or RPV C0avg between the two age groups (Table 1).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…These steady‐state values (C0 at all timepoints and C0avg) were above the pharmacologically active concentrations 11–13 (DTG PA‐IC90 = 0.064 μg mL −1 as well as the clinical target C0 of 0.3 μg mL −1 ; RPV PA‐IC90 = 12 ng mL −1 ) at all timepoints in both the overall population and the NNRTI subset (Figure 2). RPV C0 and Cavg were also at or above 70 ng mL −1 (the lowest C0 value of 68.91 ng mL −1 occurred at week 4 in the early‐switch group of the NNRTI subset), which was recently proposed by others as the clinical target from an observational cohort of treatment‐naive and treatment‐experienced people with HIV‐1 14 . The categorical analysis exploring the effect of age (≥50 and <50 years) on PK did not reveal any clinically meaningful differences in the DTG or RPV C0avg between the two age groups (Table 1).…”
Section: Resultsmentioning
confidence: 87%
“…12 those with virologic suppression after 6 months (72 vs 97 ng mL À1 , P = .03) and 12 months (68 vs 103 ng mL À1 , P = .006), which could have been in part related to suboptimal adherence, but RPV C0 levels remained well above PA-IC90 regardless of virologic suppression status. 14 The absence of a PK/PD relationship was also the case for the NNRTI subset, despite the slightly lower C0 values in the immediate post-switch period due to residual enzyme induction by EFV or NVP taken prior to the switch, supporting a direct switch to the 2DR DTG + RPV from any antiretroviral regimen without dose adjustment, lending more support for the approved doses that are efficacious when administered as part of a two-or three-drug regimen. This finding is consistent with prior studies in which participants were immediately switched from a three-drug regimen containing an enzyme inducer to a three-drug regimen containing DTG or RPV.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Current target trough concentration (C trough ) for rilpivirine is 0.05 mg/L (Néant et al, 2020), which is suggested as four times the concentration required for 90% inhibition (IC 90 0.012 mg/L) (Margolis et al, 2015). However, a recent study with rilpivirine based regimen have highlighted that the current C trough target might need to be reassessed (Néant et al, 2019) and an optimal target C trough of 0.07 mg/L is required to achieve virologic response, especially in pre-treated patients (Néant et al, 2020). This is further complicated considering that 11% of a population in Aouri et al study did not reach a C trough of 0.05 mg/L (Aouri et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Current target trough concentration (C trough ) for rilpivirine is 0.05 mg/L ( Néant et al, 2020 ), which is suggested as four times the concentration required for 90% inhibition (IC 90 0.012 mg/L) ( Margolis et al, 2015 ). However, a recent study with rilpivirine based regimen have highlighted that the current C trough target might need to be reassessed ( Néant et al, 2019 ) and an optimal target C trough of 0.07 mg/L is required to achieve virologic response, especially in pre-treated patients ( Néant et al, 2020 ). This is further complicated considering that 11% of a population in Aouri et al study did not reach a C trough of 0.05 mg/L ( Aouri et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%